2013
DOI: 10.1007/s00586-013-2865-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relationship between cervical spinal canal stenosis and traumatic cervical spinal cord injury without major fracture or dislocation

Abstract: Purpose The purpose of the study was to evaluate the clinical relationship between cervical spinal canal stenosis (CSCS) and incidence of traumatic cervical spinal cord injury (CSCI) without major fracture or dislocation, and to discuss the clinical management of traumatic CSCI. Methods Forty-seven patients with traumatic CSCI without major fracture or dislocation (30 out of 47 subjects; 63.83 %, had an injury at the C3-4 segment) and 607 healthy volunteers were measured the sagittal cerebrospinal fluid (CSF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 19 publications
(24 reference statements)
2
25
1
1
Order By: Relevance
“…This is not a surprising finding, because a male predominance as high as 72% to 96% was also reported in other series (1,7,10,11,14). This is probably due to male dominance in both spinal cord injury and cervical canal stenosis, especially in OPLL.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This is not a surprising finding, because a male predominance as high as 72% to 96% was also reported in other series (1,7,10,11,14). This is probably due to male dominance in both spinal cord injury and cervical canal stenosis, especially in OPLL.…”
Section: Discussionsupporting
confidence: 79%
“…The management of these patients is controversial. Some authors preferred to follow them without any treatment (14), while others recommended preventive decompression surgery to avoid catastrophic consequences of spinal trauma (1). Results of our study showed that most of the patients with SCI-associated CSCS are asymptomatic before injury, and rates of mortality and morbidity are very high.…”
Section: Discussionmentioning
confidence: 83%
“…Cervical spinal cord injury without fracture and dislocation (CSCIWFD) is a special type of cervical injury that refers to injuries from external force resulting in patients having clinical signs and symptoms but without abnormal radiographic or CT evidence. Most patients are elderly and have radiographic abnormalities such as osteophyte, disc herniation, hypertrophy of the ligamentum flavum, or ossification of the posterior longitudinal ligament, which can cause stenotic spondylotic canal and spinal cord compression.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of cervical myelopathy was 10.1 % in participants with spinal canal diameters of B13 mm. In the elderly, traumatic cervical spinal cord injury without major fracture or dislocation is a common cause of spinal cord injury, with a reported incidence of 10-16 % in North America [80]. In Japan, the annual incidence of traumatic cervical spinal cord injury without major fracture or dislocation has been estimated to be 3000-10,000 persons per year and is increasing dramatically in Japan [80,81].…”
Section: Etiologymentioning
confidence: 99%